Integrating Poetry in ELT: Enhancing Linguistic and Aesthetic Appreciation - A Systematic Literature Review - Rahman Efendi; Wiwin Suriani; Nurul Izzah; Amaluddin (JELITA, 2024)
This article aims to review the literature on integrating poetry in English language learning (ELT) and evaluate how this can enhance linguistic and aesthetic appreciation among students. It seeks to identify the benefits, challenges, as well as best practices in the use of poetry as a pedagogical tool in ELT. This review used a systematic literature search method with databases such as Google Scholar, Mendeley, Science Direct, Taylor & Francis Online and other academic journals, using keywords such as “poetry in ELT”, “linguistic appreciation”, and “aesthetic appreciation”. Articles were selected based on strict inclusion and exclusion criteria and then analyzed qualitatively to identify key themes and findings. The findings show that integrating poetry in ELT provides some significant benefits, including increased vocabulary, grammatical understanding, and phonological awareness. In addition, poetry also enriches students' aesthetic experience, enhances cultural appreciation, and promotes emotional engagement and creativity. However, challenges such as teachers' lack of preparedness and limited teaching materials require further attention. The use of poetry in ELT has great potential to enrich students' learning experiences both linguistically and aesthetically. The practical implications for teaching and curriculum development are extensive, and further research is needed to address the existing challenges and explore more effective teaching strategies.